Structural and functional analysis of hypothetical and conserved proteins of Clostridium tetani - Shymaa Enany (Elsevier, 2014)
Summary: The progress in biological technologies has led to rapid accumulation of microbial genomic sequences with a vast number of uncharacterized genes. Proteins encoded by these genes are usually uncharacterized, hypothetical, and/or conserved. In Clostridium tetani (C. tetani), these proteins constitute up to 50% of the expressed proteins. In this regard, understanding the functions and the structures of these proteins is crucially important, particularly in C. tetani, which is a medically important pathogen. Here, we used a variety of bioinformatics tools and databases to analyze 10 hypothetical and conserved proteins in C. tetani. We were able to provide a detailed overview of the functional contributions of some of these proteins in several cellular functions, including (1) evolving antibiotic resistance, (2) interaction with enzymes pathways, and (3) involvement in drug transportation. Among these candidates, we postulated the involvement of one of these hypothetical proteins in the pathogenic activity of tetanus. The structural and functional prediction of these proteins should serve in uncovering and better understanding the function of C. tetani cells to ultimately discover new possible drug targets. Keywords: Clostridium tetani, Hypothetical proteins, Conserved proteins, Structure, Function, Bioinformatics